Review of the planthopper genus Ommatissus Fieber (Hemiptera: Fulgoromorpha: Tropiduchidae) with descriptions of three new species from China - Chang, Zhi-Min; Chen, Xiang-Sheng (Zootaxa, 2014)
The tropiduchid planthopper genus Ommatissus Fieber, 1875 is reviewed to include six species in China: O. binotatus Fieber, 1875 (Taiwan), O. chinsanensis Muir, 1913 (Hong Kong, Macao, Guangdong), O. fuscus sp. nov. (Guizhou, Yunnan, Hunan), O. lateralis sp. nov. (Yunnan, Guizhou), O. lofouensis Muir, 1913 (Guizhou, Shandong, Shanxi, Hunan, Zhejiang, Fujian, Taiwan) and O. trimaculatus sp. nov. (Yunnan). Except O. chinsanensis and O. binotatus, four species are described or redescribed and illustrated. The generic characters are redefined. A checklist and key to all species in the genus are provided.